Magnetic nanoparticle technique versus radioisotope technique in detection of sentinel lymph node in early breast cancer: a systematic review and meta-analysis - Salman, Muhammad; Macano, Christina; Sharma, Rishabha D.; Antequerra, Alfonso (International Surgery Journal, 2021)
Sentinel lymph node biopsy is the standard technique to stage the axilla in early breast cancer. The gold standard is the dual technique of radioisotope and blue dye injection. The drawbacks of dual technique include handling and disposal of radioactive material. Equally reliable, user and patient friendly, magnetic tracer super paramagnetic iron oxide, was compared with the radioisotope tracer in detection of Sentinel lymph node in a clinically node negative axilla in early breast cancer in this meta-analysis, with emphasis on the utility and safety of both techniques. PubMed, Medline were searched from April 2015 to October 2019. 1395 patients’ data was included from seven homogenous studies in this meta-analysis. A statistical analysis was performed using STATA 16.1 version for sentinel lymph node detection rate using standard technique, magnetic tracer technique and both techniques. Ratio of successes and failures of the outcomes was measured and analysed. A paired two sample ‘Z’ test was performed to compare between the standard technique and magnetic tracer techniques. The standardised mean difference of ratio of success rate between two techniques was; 1.013334 with a p value of 0.3136.The standardised mean difference of ratio of failure rate between two techniques was 1.016667, with a p value of 0.3132. Success and failure rate showed statistically no significant difference between the two techniques. This two-way analysis with paired two sample ‘Z’ test confirms that neither standard technique nor magnetic tracer techniques are superior or inferior to each other.